PERAN PASAR DESA DALAM MENINGKATKAN TARAF EKONOMI MASYARAKAT MENURUT PERSPEKTIF EKONOMI ISLAM: (Studi Pada Masyarakat Desa Tulungagung Kecamatan Kertasemaya Kabupaten Indramayu) - Arwani, Arwani (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2021)
The aim of this research is to determine the role of markets in improving society's economy according to an Islamic Economics perspective. With this type of field research (Field Research) and a qualitative approach with descriptive methods. Data collection techniques include observation, interviews and documentation with traders, village heads and market coordinators. The research results found that: (1) The village market in Tulungagung Village, Kertasemaya District, Indramayu Regency plays a very important role for traders, both traders from the Tulungagung village community and traders from other villages. (2) Tulungagung Market is useful as a place to sell merchandise and a place for buying and selling transactions between traders and buyers. (3) Obstacles in developing the Tulungagung market are market cleanliness, market order and security, diversity of types of merchandise, availability of stalls for traders, and operational hours of the Tulungagung village market.